Fragilidade física e social de pacientes com doença renal crônica em tratamento hemodialítico e transplante renal - Santos, Diana Gabriela Mendes dos (2022)
Frailty is strongly prevalent in patients with Chronic Kidney Disease (CKD), with those on dialysis being the most fragile. In addition, the literature points out that frailty is associated with a higher risk of hospitalization and mortality in patients with CKD. Although there is a very strong conception of frailty from a physical point of view, it is not an exclusively physical syndrome, encompassing biopsychosocial factors that depend on a holistic view of the frail individual. Social fragility consists of the decline of social relationships and social support that are directly linked to life course determinants. The CKD process from diagnosis to treatment leads to several biopsychosocial changes in the patient's life, directly impacting activities and social participation. In addition, it is known that the social support received by this population, in most cases, is fragmented and insufficient. n view of the above, this study aimed to compare the relationship between the physical and social frailty of patients undergoing hemodialysis (HD) and renal transplantation (TX). This research is a correlational, comparative, cross-sectional study with a quantitative approach. The sample size was 284 patients. For data collection, the following instruments were used: sociodemographic, economic and health status, Tilburg Frailty Indicator (TFI), HALFT Social Frailty Assessment Scale, Patient Health Questionnaire-9 (PHQ-9) and Support Scale Social of the Medical Outcomes Study (MOS). Among the results found, there was a higher prevalence of physical frailty (HD:93% and TX:54.9%; coef=-1.19; P<0.001) and social frailty (HD:51.2% and TX:24 .0%; coef.= -0.82; P<0.001) for the HD group. The HD group had a higher level of depression (Beta = -0.31 with 95%CI: - 0.56, -0.07) than the TX group. Depression had a moderate effect (Beta = 0.51 with 95%CI: 0.40, 0.61) on physical frailty, and social support had a small protective effect on social frailty (Beta = -0.40 with 95%CI: -0.50, -0.30). Furthermore, social frailty has a moderate effect on depression (Beta = 0.56 with 95%CI: 0.46, 0.66). It is concluded that HD patients were more physically and socially fragile and more depressed compared to TX patients. In addition, an association of physical frailty with depression and social frailty with social support and depression was confirmed.